Evolution of Ethosomes In Pharmaceutical Sciences: From Basic Vesicles To Advanced Nanocarrier Systems - Salunke Harshada; Dr.Hangargekar Sachin; Ankita Gadhave (Asian Journal of Pharmaceutical Research and Development, 2026)
Transdermal drug delivery systems (TDDS) have emerged as an effective alternative to conventional drug administration by overcoming limitations such as poor bioavailability, gastrointestinal degradation, and hepatic first-pass metabolism. Among various vesicular carriers, ethosomes have gained significant attention due to their superior ability to enhance drug permeation through the skin. Ethosomes are soft, flexible phospholipid vesicles containing high concentrations of ethanol, which increase membrane fluidity and disrupt the lipid organization of the stratum corneum, facilitating deeper skin penetration. They can efficiently encapsulate hydrophilic, lipophilic, and amphiphilic drugs, enabling controlled and sustained drug release with improved therapeutic efficacy and patient compliance. Since their introduction by Touitou and co-workers in the late 1990s, ethosomes have been extensively investigated for the delivery of anti-inflammatory, antifungal, antiviral, hormonal, anticancer, and peptide-based therapeutics. This review highlights the history, composition, mechanism of skin penetration, methods of preparation, characterization techniques, advantages, limitations, and diverse pharmaceutical applications of ethosomes. Recent advancements, including Nanoethosomes, ligand-modified systems, and integration with hydrogels and microneedles, have further expanded their potential in targeted and personalized drug delivery. Overall, ethosomes represent a promising and versatile carrier system for enhanced transdermal and topical therapy.